The Place of Forensic Accounting in External Audit Practice (International Journal of Scientific Research and Management (IJSRM), 2023)
This study focused on the place of forensic accounting in external audit practice. The need for auditing was necessitated following separation of ownership from control. Auditing requires the external auditor to carry out an unbiased examination and investigation of the financial statement of any firm with a view to express an opinion on its truth and fairness in accordance. On the other hand, forensic accounting or auditing is a special audit for the purpose of litigation in the court of law. This implied that it required special methodological approach which is completely different from traditional or ordinary audit practice. Hence, this study specifically examined the need, skills, practice of forensic accounting and the relationship between forensic and traditional accountants or auditors. It is a library type of research. It solely employed secondary source of information. Information were obtained from textbooks, Journal articles, seminar papers, thesis etc. Having examined various related literature, it was revealed that the need for forensic accounting was to track crimes in various ways for the purpose of litigation in the court room and it is absolutely different from traditional audit because of exceptional skills required which can enhance external audit practice. It recommended that all professional accountants or practicing accountants should acquire knowledge in forensic accounting skills and all universities should run degree course in forensic accounting in order to aid knowledge of forensic skills in Nigeria.